Age Differences in Engagement in Hong Kong Anti-Extradition Bill Protest: The Role of Self-Relevance. (16th December 2020) - Wong, Tze Kiu; Tse, Dwight C K; Fung, Nicole Long Ki; Fung, Helene
Abstract: Older adults were found to be less involved in non-institutional political actions than younger people did, and our previous work found that self-relevance mediated this age difference. In this study, we attempted to replicate the finding in a real-life social movement. We recruited 1037 participants (aged 18-84) during the anti-extradition bill movement in Hong Kong in September 2019. They responded to questions of how relevant and important the movement was to them, and whether they had taken part in a list of 8 political actions (e.g. signing petitions, joining rallies). Older adults indeed participated less in the movement compared with younger adults, and the age difference could partly be attributed to a lower perceived relevance of the movement. The finding suggested emphasizing on self-relevance as a potential way to promote political participation in older adults.